2020
DOI: 10.48550/arxiv.2001.03994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast is better than free: Revisiting adversarial training

Eric Wong,
Leslie Rice,
J. Zico Kolter

Abstract: Adversarial training, a method for learning robust deep networks, is typically assumed to be more expensive than traditional training due to the necessity of constructing adversarial examples via a first-order method like projected gradient decent (PGD). In this paper, we make the surprising discovery that it is possible to train empirically robust models using a much weaker and cheaper adversary, an approach that was previously believed to be ineffective, rendering the method no more costly than standard trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
182
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(183 citation statements)
references
References 28 publications
1
182
0
Order By: Relevance
“…We observed that addition of random augmentation further improves the results of our method. Our method outperforms both Free [67] and Fast [80] AT in accuracy and robustness, significantly.…”
Section: Transferring Robustness Without Adversarial Examplesmentioning
confidence: 88%
See 2 more Smart Citations
“…We observed that addition of random augmentation further improves the results of our method. Our method outperforms both Free [67] and Fast [80] AT in accuracy and robustness, significantly.…”
Section: Transferring Robustness Without Adversarial Examplesmentioning
confidence: 88%
“…For Table 1, we take clean accuracy and auto-attack results from [18] and PGD-100 results are the best PGD attack reported results (with the same or similar setting as ours) taken from the respective papers. For Table 2, we take Shafahi et al [67], Wong et al [80]'s reported results and evaluated our model with the same settings of PGD attack. For Table 3, we train the same models with PGD7-AT [50], RKD [26] and our method.…”
Section: A1 Additional Details Of Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep models are vulnerable to adversarial examples that are maliciously constructed to mislead the models to output wrong predictions but visually indistinguishable from normal samples [182]- [185]. Adversarial training [186]- [188] is one of the most effective approaches to defend deep models against adversarial examples and enhance their robustness. Its main idea is to augment training data with existing adversarial example generation methods during the training process.…”
Section: B Collaborative Adversarial Trainingmentioning
confidence: 99%
“…For example, Shafahi et al [186] proposed an efficient adversarial training algorithm that recycles the gradient information computed at each iteration to eliminate the overhead cost of generating adversarial examples. Wong et al [188] propose to utilize Fast Gradient Sign Method (FGSM) [182] during the adversarial training process. They introduce random initialization points to improve the effectiveness the projected gradient descent based training.…”
Section: B Collaborative Adversarial Trainingmentioning
confidence: 99%